Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.rmed.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Causes of misdiagnosis of chronic obstructive pulmonary disease: A systematic scoping review

Abstract: The causes of misdiagnosis of COPD are attributable mainly to spirometry and to the healthcare professional performing the diagnostic assessment. With a view to limiting misdiagnosis of COPD, future research should help clarify strategies for alternative objective tests for determining if a patient has COPD and explore how to better support primary care in the diagnosing of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 80 publications
0
49
0
2
Order By: Relevance
“…COPD misdiagnosis and misclassification has been linked to the threshold for defining obstruction and is widely discussed. [5][6][7][8][9][10][11][12] Moreover, COPD misdiagnosis and misclassification may be caused by the use of pre-bronchodilator spirometry instead of post-bronchodilator spirometry. A false positive diagnosis of COPD can lead to harmful treat-ment for a patient without COPD as well as unawareness of and therefore no treatment for other possible reasons causing the underlying air-flow obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…COPD misdiagnosis and misclassification has been linked to the threshold for defining obstruction and is widely discussed. [5][6][7][8][9][10][11][12] Moreover, COPD misdiagnosis and misclassification may be caused by the use of pre-bronchodilator spirometry instead of post-bronchodilator spirometry. A false positive diagnosis of COPD can lead to harmful treat-ment for a patient without COPD as well as unawareness of and therefore no treatment for other possible reasons causing the underlying air-flow obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Spirometry criteria are also an important factor in COPD diagnosis. 21 GOLD argues that the threshold of post-bronchodilator FEV 1 /FVC Ͻ 0.7 should remain, 22 whereas multiple studies argue that LLN should be used as an alternative threshold for defining COPD. [23][24][25][26][27] Woodruff et al 28 found that current or former smokers who did not meet the existing criteria for COPD had evidence of airway disease.…”
Section: Discussionmentioning
confidence: 99%
“…La calidad técnica de la espirometría es muy significativa por cuanto una prueba mal hecha podría inducir a errores de interpretación tanto en el diagnóstico como en el tratamiento (10,11). La Asociación Latinoamericana de Tórax (ALAT) viene trabajando desde hace más de 20 años para unificar criterios y mejorar la calidad de la espirometría (12).…”
Section: Evaluación De Discapacidad: • Pacientes Candidatos a Programunclassified